(untitled) (INNOVATIVE ECONOMY, 2024)
Yurchyshyn O.Ya., Seminska N.V., Romashko A.S. ANALYSIS OF THE STATE OF INNOVATIVE SOLUTIONS IN THE FIELD OF PROSTHETICS Purpose. The purpose of the article is to determine the state of innovative solutions for prosthetics technologies, in particular using 3D printing, in Ukraine and the world, based on the patent information search. Methodology of research. The abstract and logical method was used to achieve this goal in aim to develop the needs and status of innovative solutions in the field of prosthetics; comparative and economic method - to analyse the domestic and world experience of introducing innovative products in the field of prosthetics; statistical analysis and generalization - to conduct a patent information search and formulate the relevant conclusions of the study. Findings. The article analyses the prosthetics and rehabilitation industry in Ukraine and the world, defines the landscape and analyses the needs to meet the market of a new industry sector for Ukraine. Based on the patent information research conducted according to the formed search query, the results show that the dynamics of patenting prosthetic technologies in the world is positive and has peaked in recent years. The companies that occupy a leading role in the prosthetics market are identified and their quantitative patent portfolios are visualized. The number of patents related to the use of new 3D printing technologies was determined by a refined search query. A separate search and analysis of patent solutions in Ukraine was carried out, which shows the absence of valid patents for industrial property rights in the field of prosthetics, which is a negative factor for prosthetic companies, people who need prosthetics and the innovation ecosystem of Ukraine in general. Originality. The practical and methodological foundations for the development of the prosthetic industry in Ukraine, the actualization of the creation of competitive prosthetic solutions, which should be acquired as objects of intellectual property rights, are substantiated, and recommendations for the development of new technologies in Ukraine through the system of RnD centres are provided. Practical value. The results of the conducted patent information research can be used in planning strategies for the creation of intellectual property rights, in finding partners from other countries for the exchange of experience and potential cooperation, and in determining the state of the art of innovative technologies in general. As a way to improve the quality of products of prosthetic enterprises and the possibility of wide scaling of technologies, it is proposed to create RnD centres where it will be possible to create a prototype and test it before production. Faster delivery of a new result will help many people to receive high-quality prostheses, which is directly related to the quality of their lives. Key words: innovation, patent, enterprise, prosthesis, additive technologies, RnD centre.